Relationship between corrosion and nanoscale friction on a metallic glass - Ma, Haoran; Bennewitz, Roland (Beilstein Journal of Nanotechnology, 2022)
Metallic glasses are promising materials for microdevices, although corrosion and friction limit their effectiveness and durability. We investigated nanoscale friction on a metallic glass in corrosive solutions after different periods of immersion time using atomic force microscopy to elucidate the influence of corrosion on nanoscale friction. The evolution of friction upon repeated scanning cycles on the corroded surfaces reveals a bilayer surface oxide film, of which the outer layer is removed by the scanning tip. The measurement of friction and adhesion allows one to compare the physicochemical processes of surface dissolution at the interface of the two layers. The findings contribute to the understanding of mechanical contacts with metallic glasses under corrosive conditions by exploring the interrelation of microscopic corrosion mechanisms and nanoscale friction.
Keywords: atomic force microscopy (AFM); corrosion; friction; metallic glass; passive film

(untitled) - Inoue, A.; Shen, B. L.; Chang, C. T. (Acta Mater., 2004)

(untitled) - Trexler, M. M.; Thadhani, N. N. (Prog. Mater. Sci., 2010)

(untitled) - Tao, P. J.; Yang, Y. Z.; Ru, Q. (J. Alloys Compd., 2010)

(untitled) - Segu, D. Z.; Choi, J. H.; Yi, S.; Kim, S. S. (Tribol. Lett., 2012)

(untitled) - Greer, A. L.; Rutherford, K. L.; Hutchings, I. M. (Int. Mater. Rev., 2002)

(untitled) - Madge, S. V.; Caron, A.; Gralla, R.; Wilde, G.; Mishra, S. K. (Intermetallics, 2014)

(untitled) - Hofmann, D. C.; Andersen, L. M.; Kolodziejska, J.; Roberts, S. N.; Borgonia, J.-P.; Johnson, W. L.; Vecchio, K. S.; Kennett, A. (Adv. Eng. Mater., 2017)

(untitled) - Jones, M. R.; Kustas, A. B.; Lu, P.; Chandross, M.; Argibay, N. (Tribol. Lett., 2020)

(untitled) - Duan, G.; Wiest, A.; Lind, M. L.; Li, J.; Rhim, W.-K.; Johnson, W. L. (Adv. Mater. (Weinheim, Ger.), 2007)

(untitled) - Hu, Q.; Fu, M. W.; Zeng, X. R. (Mater. Des., 2014)

(untitled) - Kumar, G.; Tang, H. X.; Schroers, J. (Nature, 2009)

(untitled) - Togashi, N.; Ishida, M.; Nishiyama, N.; Inoue, A. (Rev. Adv. Mater. Sci., 2008)

(untitled) - Wang, Y.; Jiang, S. L.; Zheng, Y. G.; Ke, W.; Sun, W. H.; Wang, J. Q. (Corros. Sci., 2012)

(untitled) - Duarte, M. J.; Klemm, J.; Klemm, S. O.; Mayrhofer, K. J. J.; Stratmann, M.; Borodin, S.; Romero, A. H.; Madinehei, M.; Crespo, D.; Serrano, J.; Gerstl, S. S. A.; Choi, P. P.; et al. (Science, 2013)

(untitled) - Si, J. J.; Chen, X. H.; Cai, Y. H.; Wu, Y. D.; Wang, T.; Hui, X. H. (Corros. Sci., 2016)

(untitled) - Jiang, X.; Song, J.; Su, Y.; Fan, H.; Zhang, Y.; Hu, L. (Tribol. Int., 2019)

(untitled) - Jiang, X.; Song, J.; Fan, H.; Su, Y.; Zhang, Y.; Hu, L. (Tribol. Int., 2020)

(untitled) - Caron, A.; Qin, C. L.; Gu, L.; González, S.; Shluger, A.; Fecht, H.-J.; Louzguine-Luzgin, D. V.; Inoue, A. (Nanotechnology, 2011)

(untitled) - Louzguine-Luzgin, D. V.; Nguyen, H. K.; Nakajima, K.; Ketov, S. V.; Trifonov, A. S. (Mater. Lett., 2016)

(untitled) - Kang, S. J.; Rittgen, K. T.; Kwan, S. G.; Park, H. W.; Bennewitz, R.; Caron, A. (Friction, 2017)

(untitled) - Ma, H.; Bennewitz, R. (Tribol. Int., 2021)

(untitled) - Green, B. A.; Steward, R. V.; Kim, I.; Choi, C. K.; Liaw, P. K.; Kihm, K. D.; Yokoyama, Y. (Intermetallics, 2009)

(untitled) - Wang, D. P.; Wang, S. L.; Wang, J. Q. (Corros. Sci., 2012)

(untitled) - Zhang, C.; Chan, K. C.; Wu, Y.; Liu, L. (Acta Mater., 2012)

(untitled) - Ma, H. R.; Li, J. W.; Chang, C. T.; Wang, X. M.; Li, R. W. (J. Therm. Spray Technol., 2017)

(untitled) - Wang, Y. M.; Zhang, C.; Liu, Y.; Chan, K. C.; Liu, L. (Intermetallics, 2013)

(untitled) - Li, W.; Li, D. Y. (Acta Mater., 2006)

(untitled) - Reffass, M.; Sabot, R.; Jeannin, M.; Berziou, C.; Refait, P. (Electrochim. Acta, 2009)

(untitled) - Yohai, L.; Schreiner, W.; Vázquez, M.; Valcarce, M. B. (Electrochim. Acta, 2016)

(untitled) - Macdonald, D. D. (J. Electrochem. Soc., 1992)

(untitled) - Sennour, M.; Marchetti, L.; Martin, F.; Perrin, S.; Molins, R.; Pijolat, M. (J. Nucl. Mater., 2010)

(untitled) - Maurice, V.; Peng, H.; Klein, L. H.; Seyeux, A.; Zanna, S.; Marcus, P. (Faraday Discuss., 2015)

(untitled) - Zhao, S.; Shi, S.; Xia, K.; Wang, T.; Chai, M.; Zhang, Y.; Qu, C.; Zheng, Q. (ACS Appl. Nano Mater., 2020)

(untitled) - Cheng, S.; Robbins, M. O. (Tribol. Lett., 2010)

(untitled) - Szlufarska, I.; Chandross, M.; Carpick, R. W. (J. Phys. D: Appl. Phys., 2008)

(untitled) - Gregori, J.; García-Jareño, J. J.; Giménez-Romero, D.; Vicente, F. (J. Electrochem. Soc., 2006)

(untitled) - Ha, H.-Y.; Kwon, H.-S. (J. Electrochem. Soc., 2012)

(untitled) - Kumar, N.; Andersson, M. P.; van den Ende, D.; Mugele, F.; Siretanu, I. (Langmuir, 2017)

(untitled) - Guo, Y.; Siretanu, I.; Zhang, Y.; Mei, B.; Li, X.; Mugele, F.; Huang, H.; Mul, G. (J. Mater. Chem. A, 2018)

(untitled) - Liu, J.-C.; Park, S.; Nagao, S.; Nogi, M.; Koga, H.; Ma, J.-S.; Zhang, G.; Suganuma, K. (Corros. Sci., 2015)

(untitled) - Boudellioua, H.; Hamlaoui, Y.; Tifouti, L.; Pedraza, F. (Appl. Surf. Sci., 2019)

(untitled) - Macdonald, D. D. (Electrochim. Acta, 2011)

(untitled) - BenSalah, M.; Sabot, R.; Triki, E.; Dhouibi, L.; Refait, P.; Jeannin, M. (Corros. Sci., 2014)

(untitled) - Choudhary, L.; Wang, W.; Alfantazi, A. (Metall. Mater. Trans. A, 2016)

(untitled) - Wang, X.; Wang, B.; Zhang, L.; Yang, C.; Yang, Y. (Metals (Basel, Switz.), 2017)

(untitled) - Shockley, J. M.; So, C. R.; Strom, M. J.; Auyeung, R. C. Y.; Horton, D. J.; Wahl, K. J. (ACS Appl. Mater. Interfaces, 2020)

Scanning probe microscopy: The Lab on a Tip - Meyer, E.; Hug, H. J.; Bennewitz, R. (Springer, 2004)

(untitled) - Bei, H.; Xie, S.; George, E. P. (Phys. Rev. Lett., 2006)

(untitled) - Yoo, B.-G.; Park, K.-W.; Lee, J.-C.; Ramamurty, U.; Jang, J.-i. (J. Mater. Res., 2009)

(untitled) - Zhang, H. W.; Subhash, G.; Jing, X. N.; Kecskes, L. J.; Dowding, R. J. (Philos. Mag. Lett., 2006)

Springer Handbook of Condensed Matter and Materials Data - Martienssen, W.; Warlimont, H. (Springer Berlin Heidelberg, 2005)